2014
DOI: 10.1158/0008-5472.can-13-3156
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Melatonin Disruption by Exposure to Light at Night Drives Intrinsic Resistance to Tamoxifen Therapy in Breast Cancer

Abstract: Resistance to endocrine therapy is a major impediment to successful treatment of breast cancer. Preclinical and clinical evidence links resistance to anti-estrogen drugs in breast cancer cells with the overexpression and/or activation of various pro-oncogenic tyrosine kinases. Disruption of circadian rhythms by night shift work or disturbed sleep-wake cycles may lead to an increased risk of breast cancer and other diseases. Moreover, light exposure at night (LEN) suppresses the nocturnal production of melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
158
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(176 citation statements)
references
References 48 publications
15
158
1
1
Order By: Relevance
“…Following this study, in 1997, Bartsch and his colleagues reported a reverse correlation between melatonin concentrations and the tumor progression rate, suggesting that the urine amount of 6-sulfatoxymelatonin (melatonin metabolite) is lower in women suffering from breast cancer compared to healthy volunteers [9]. Further clinical investigations pointed out a reverse correlation between decrease nocturnal melatonin plasma level and the incidence of estrogen receptor positive type breast cancer, suggesting the administration of melatonin may be particularly advantageous to these patients [10][11][12]. Moreover, it has been established that disrupt the circadian rhythm of the melatonin level by some factors, including light at night, sleep deprivation, shift work, chronic jet lag, mutations in melatonin genes and ageing may increase susceptibility of normal breast cells to oxidative damages, leading to an increased risk of breast cancer mostly through elevated secretion of the activated cytokines [13].…”
Section: Introductionmentioning
confidence: 81%
“…Following this study, in 1997, Bartsch and his colleagues reported a reverse correlation between melatonin concentrations and the tumor progression rate, suggesting that the urine amount of 6-sulfatoxymelatonin (melatonin metabolite) is lower in women suffering from breast cancer compared to healthy volunteers [9]. Further clinical investigations pointed out a reverse correlation between decrease nocturnal melatonin plasma level and the incidence of estrogen receptor positive type breast cancer, suggesting the administration of melatonin may be particularly advantageous to these patients [10][11][12]. Moreover, it has been established that disrupt the circadian rhythm of the melatonin level by some factors, including light at night, sleep deprivation, shift work, chronic jet lag, mutations in melatonin genes and ageing may increase susceptibility of normal breast cells to oxidative damages, leading to an increased risk of breast cancer mostly through elevated secretion of the activated cytokines [13].…”
Section: Introductionmentioning
confidence: 81%
“…The oncostatic effect of melatonin in breast cancer is thought be mediated through its anti-estrogenic actions as well as its role in regulating the activity of aromatases, the enzymes responsible for the local biosynthesis of estrogens from androgens (Cos et al 2006). Recent studies using MCF-7 breast cancer xenografts in mice showed that suppression of melatonin production by dim light exposure at night leads to both tamoxifen (Dauchy et al 2014) and doxorubicin resistance (Xiang et al 2015).…”
Section: Nuclear Receptors In Breast Cancermentioning
confidence: 99%
“…In fact, we are not aware of specifi c assessments of SF in patient cohorts and cancer, although there is substantial indirect evidence from studies demonstrating that long-term night workers and shift workers have increased incidence of solid malignancies 59,60 that appear to be attributable, at least partly, to reduced melatonin secretion. [61][62][63] Similarly, the cumulative evidence gathered thus far would suggest that sleep duration is an important factor in cancer incidence and outcomes. In a series of meta-analyses, shift work was strongly associated with a higher risk of breast cancer, [64][65][66] but most if not all the studies had major sociodemographic factors and comorbidity confounders (including obesity and metabolic disease).…”
Section: What About Sf?mentioning
confidence: 99%